The German CArdioSurgEry Atrial Fibrillation Registry: In-Hospital Outcomes - Wehbe, Mahmoud; Albert, Marc; Lewalter, Thorsten; Ouarrak, Taoufik; Senges, Jochen; Hanke, Thorsten; Doll, Nicolas; on behalf of the CASE-AF Investigators (The Thoracic and Cardiovascular Surgeon, 2021)
Background The aim of this study was to describe outcomes of patients undergoing surgical ablation for atrial fibrillation (AF) as either stand-alone or concomitant cardiosurgical procedures in Germany.Methods Patients with AF undergoing concomitant or stand-alone surgical ablation were included in the registry. Cardiac surgery centers across Germany were invited to participate and sought to enroll 1,000 consecutive patients. Data was obtained through electronic case report forms. The protocol mandated follow-up interviews at 1 year.Results Between January 2017 and April 2020, 17 centers enrolled 1,000 consecutive patients. Among concomitant surgical patients (n = 899), paroxysmal AF was reported in 55.4% patients. Epicardial radio frequency (RF) bilateral pulmonary vein isolation (PVI) with excision of the left atrial appendage (LAA) was the most common operative strategy. In the stand-alone cohort (n = 101), persistent AF forms were reported in 84.1% of patients. Moderate-to-severe symptoms were reported in 85.1%. Sixty-seven patients had previously underwent at least two failed catheter ablative procedures. Thoracoscopic epicardial RF bilateral PVI and completion of a “box-lesion” with LAA closure were frequently preformed. Major cardiac and cerebrovascular complications occurred in 38 patients (4.3%) in the concomitant group. No deaths were reported in the stand-alone group. At discharge, sinus rhythm was achieved in 88.1% of stand-alone and 63.4% concomitant patients.Conclusion The CArdioSurgEry Atrial Fibrillation registry provides insights into surgical strategies for AF ablation in a considerable cohort across Germany. This in-hospital data demonstrates that concomitant and stand-alone ablation during cardiac surgery is safe and effective with low complication rates.
Keywords: arrhythmia therapy; heart valve surgery; minimally invasive surgery